Legendary Retail Brands : a sustainable business model? - Soicher, Antony; Beswick, Claire (London : Wits Business School, 2016)
With many years of experience as an entrepreneur and businessman, Alan Reeves, chief operating officer (COO) of Legendary Retail Brands (LRB), which was the shareholder and administrator of the Mica, DIY Depot and House of Paint and D?cor voluntary buying group (VBG) brands, was continuously thinking about the next step for the group. Member profitability was good, despite a tough economic environment, but Reeves was aware that this could change easily. "That's why we need to plan ahead for the next five years," he thought. As he planned for the next board meeting in September 2016, Reeves considered the options for the group and what he could recommend regarding the way forward.
Originally published in Soicher, A., & Beswick, C. (2016). Legendary retail brands: A sustainable business model? WBS-2016-8. Johannesburg: The Case Centre, Wits Business School.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Legendary Retail Brands -- Management; Strategic planning; Stores, Retail